Food Systems Profile: Dong Anh, The peri-urban area - Vietnam. - Huynh, Thi Thanh Tuyen; Pham, Thi Mai Huong; Duong, Thi Thanh; Haan, Stef de; Hernández, Ricardo; Trinh, Thi Huong; Nguyen, Mai Trang; Even, Brice; Lundy, Mark M.; Swaans, Cornelis P.M.; Raneri, Jessica Evelyn; Hoang, The Ky; et al. (2021)
This Food Systems (FS) profile aims to provide a synopsis of the food system of the Dong Anh district in Hanoi, a peri-urban area in north Vietnam. This profile gives an overview of the main food system outcomes, constituent elements and drivers. It does so through a set of metrics that highlight key challenges and offers a baseline for the measurement and monitoring of future changes. It builds from the outcomes concerning residents’ diets, nutrition and health, socio-economics, and environment. It then traces back to the food supply chains, the food environment, consumer behavior and finally the underlying drivers. Ultimate, the profile’s goal is to help researcher and policy makers understand the existing challenges among the elements of the food systems to help develop actionable policy recommendations for local socio-economic development planning.